Birds of Summer Hill, Shimla (Himachal Pradesh) - Mattu, V. K.; Thakur, M. L. (Indian Forester, 2006)
Studies on birds of Summer Hill, Shimla (H.P.) revealed a total of 70 species, of which 64 species showed seasonal-local or long range migration and rest 6 were residents. Out of these 64 migrants, 44 were seasonal-local migrants, 15 summer visitors, 4 winter visitors and one was monsoon visitor. Further, 34 species were found to be very common, 19 common, 15 uncommon and 2 were occasional in nature. Human habitation (63) supported the highest number of species, followed by open-oak forest (52) and conifer forest (29). In addition, 17 species were exclusive to human habitation, 5 restricted to open-oak forest and rest 48 species were observed in two or more habitats. Moreover, one globally threatened (critical) and 10 biome-restricted species were observed in this area.